1999
DOI: 10.2466/pr0.1999.85.3.1025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Properties of Words and Elicitation of Skin Conductance Response

Abstract: We investigated the association of subject-rated imagery, subject-rated concreteness, subject-rated emotionality, frequency, date of entry into the language, and word length with emotional imagery as measured by the skin conductance response elicited by that word. 50 words in a list of 25 word-pairs were rated by 96 university students; then their skin conductance response of each word was measured for each word. In each pair, one word was concrete and one was abstract but with related meaning, e.g., adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We next investigated the relations between the properties evaluated in the present study (Meaningfulness, Interest value, and Familiarity) and properties of the same words as assessed by us in previous studies, namely, Imagery value, Concreteness, Emotionahty, and Skin conductance response (Campos, et al, 1999a(Campos, et al, , 1999b, and with Frequency of use, Date of entry into Spanish, and Word Length (Table 1). Meaningfulness correlated significantly with Frequency of use, Imagery, Concreteness, and Skin conductance response.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…We next investigated the relations between the properties evaluated in the present study (Meaningfulness, Interest value, and Familiarity) and properties of the same words as assessed by us in previous studies, namely, Imagery value, Concreteness, Emotionahty, and Skin conductance response (Campos, et al, 1999a(Campos, et al, , 1999b, and with Frequency of use, Date of entry into Spanish, and Word Length (Table 1). Meaningfulness correlated significantly with Frequency of use, Imagery, Concreteness, and Skin conductance response.…”
Section: Resultsmentioning
confidence: 92%
“…Word Length was measured as number of letters (Rubin, 1980;Campos & Gonzdez, 1992;Campos, et al, 1999b). Date of entry into the Spanish language was defined as the earliest year mentioned for each word in the Brwe diccionario etimoh5gico de la lengua castellana (Corominas, 1983), and Frequency of use was taken from Alameda and Cuetos (1995).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manning and Melchiori (1974) observed similar patterns of SCRs when the stimuli were words rated as highly pleasant and unpleasant compared with neutral words. Campos, Marcos, and Gonzalez (1999) investigated how SCR related to different qualities of displayed words, and they found that 30% of the variance in SCR was explained by imagery and subject-rated emotionality of the displayed words.…”
Section: Electrodermal Activitymentioning
confidence: 99%